Colloidal Nanosurfactants for 3D Conformal Printing of 2D van der Waals Materials. Issue 39 (26th August 2020) - Zeng, Minxiang; Kuang, Wenzheng; Khan, Irfan; Huang, Dali; Du, Yipu; Saeidi‐Javash, Mortaza; Zhang, Lecheng; Cheng, Zhengdong; Hoffman, Anthony J.; Zhang, Yanliang
Abstract: Printing techniques using nanomaterials have emerged as a versatile tool for fast prototyping and potentially large‐scale manufacturing of functional devices. Surfactants play a significant role in many printing processes due to their ability to reduce interfacial tension between ink solvents and nanoparticles and thus improve ink colloidal stability. Here, a colloidal graphene quantum dot (GQD)‐based nanosurfactant is reported to stabilize various types of 2D materials in aqueous inks. In particular, a graphene ink with superior colloidal stability is demonstrated by GQD nanosurfactants via the π–π stacking interaction, leading to the printing of multiple high‐resolution patterns on various substrates using a single printing pass. It is found that nanosurfactants can significantly improve the mechanical stability of the printed graphene films compared with those of conventional molecular surfactant, as evidenced by 100 taping, 100 scratching, and 1000 bending cycles. Additionally, the printed composite film exhibits improved photoconductance using UV light with 400 nm wavelength, arising from excitation across the nanosurfactant bandgap. Taking advantage of the 3D conformal aerosol jet printing technique, a series of UV sensors of heterogeneous structures are directly printed on 2D flat and 3D spherical substrates, demonstrating the potential of manufacturing geometrically versatile devices based on nanosurfactant inks. Abstract : Nanosurfactant‐stabilized 2D material inks are printed conformally on various 2D/3D substrates enabling rapid fabrication of complex device structures with high spatial resolution. Specifically, graphene quantum dot nanosurfactants not only provide electrostatic stabilization for a wide range of 2D materials, but also have become an integrated part of printed devices and result in superior mechanical/optoelectronic properties in 2D‐material‐based devices.